Upaya Meningkatkan Hasil Belajar Siswa Melalui Model Snowball Throwing dengan Media TTS pada Pembelajaran IPA Kelas IV SD Negeri 02 Koto Bangun Kecamatan Kapur IX - Elimasni Elimasni (Eduscience Development Journal, 2019)
Based on preliminary observations in class IV of SD Negeri 02 Koto Bagun, Kapur IX District, problems of science learning were found. The teacher is less varied, creative in teaching in class, only emphasizes the delivery of material and assignments. Students are less involved in learning, less enthusiastic, less motivated in discussion activities, and the use of learning media is not optimal. Formulation of the research problem "How do you increase student activity in learning science class IV SD Negeri 02 Koto Bangun Kapur District IX?". As for the specific details "Does the Snowball Throwing model with TTS media can improve teacher skills, student activities and student learning outcomes of SD Negeri 02 Koto Bangun Kapur IX District in Natural Sciences learning?". The purpose of the study was to increase student activity in learning science class IV SD 02 02 Koto Bangun Kapur District IX. The specific purpose is to describe the improvement of teacher skills, student activities and improve science learning outcomes of Grade IV students of SD Negeri 02 Koto Bangun Kapur IX District through the Snowball Throwing model with TTS media. This type of research is classroom action research, conducted in two cycles. Each cycle consists of planning, implementing actions, observing, and reflecting. The research subjects were teachers and fourth grade students of SD Negeri 02 Koto Bangun, Kapur District IX. Data collection techniques using observation, tests, field notes, and documentation. The results showed the skills of teachers in the first cycle of meeting 1 gained 29 scores, increased to 34 scores in meeting 2. In the second cycle of meeting 1 gained 37 scores, increased to 40 scores at meeting 1. The activity of cycle I students gained 21 scores, increased to 30 score at meeting 2. In cycle II gained 32 scores, increased to 37 scores at meeting 2. The percentage of mastery learning at the pre cycle was 27.27% with an average value of 69.29. In the first cycle of 63.63% with an average value of 79.09. In the second cycle of 100% with an average value of 91.82. The conclusion of the research is the Snowball Throwing model with TTS media can improve teacher skills, student activities and science learning outcomes. While the advice given is that teachers should be able to choose and use innovative learning models that are appropriate to the conditions of students, teaching materials / materials, facilities available, and the condition of the teacher himself.